The Centrality of Glocalisation in Sustaining Development Education in Ghana and Nigeria - Amponsah, S.; Babarinde, K. (researchgate, 2022)
t Since the attainment of independence from their colonial masters in 1957 and 1960, the Ghanaian and Nigerian education systems have undergone several reforms to conform to the times. Incidentally, all the reforms seem to drive the values of education towards Western philosophies. Indigenous knowledge systems, content and African forms of delivery have eluded the two countries’ educational systems. To bring back authentic African content into development education, this paper advo cates for the incorporation of local content and delivery styles to ensure learners carry the ‘knowledge of their fathers’ into the future and immortalise such knowledge for posterity. In pushing this agenda, we did a content analysis of the various educational reforms in Ghana and Nigeria. Based on what exists in the literature, we theorized that in respect of SDG 4 and the bid to sustain education as a contribution to devel opment education, glocalisation should be the prime focus. Consequently, we noted that policy directives, decolonization of the various curricula used in education and the implementation of the recommendations from earlier studies and declarations are imperatives to this call.
Research Article
Keywords: Adult education; Educational system; Decolonization; Sustainable development